Pengaruh Perilaku Birokrasi terhadap Kinerja Pegawai pada Kantor Kecamatan Salahutu Kabupaten Maluku Tengah - Sakir, Ahmad Rosandi (Penerbit Goodwood, 2024)
Purpose: The main purpose of this research is to investigate how bureaucratic behavior influences employee performance at Kecamatan Salahutu office. Methodology: This research employs a quantitative approach with a descriptive design to analyze the impact of bureaucratic behavior on employee performance. The quantitative approach was chosen because it allows for the objective measurement of variables and statistical analysis to identify relationships between independent and dependent variables. Results: The results of this study indicate a significant relationship between bureaucratic behavior and employee performance at Kecamatan Salahutu. High validity and reliability of the instruments used ensure accurate measurement of both variables. The findings demonstrate consistent improvement in employee performance when bureaucratic behavior aligns with effective practices, supporting the importance of fostering positive organizational behavior. Limitations: The limitations of this study include a limited sample size and a focus on a single district, which may affect the generalizability of the findings. Additionally, future research could explore other factors influencing bureaucratic behavior and employee performance. Contribution: This study contributes to understanding the impact of bureaucratic behavior on employee performance, providing insights for improving public service quality and fostering better organizational practices.